PI1M Managers and Asst. Managers Orientation - Universiti Malaysia Sarawak, Institute of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak (UNIMAS), 2015)
Orientation session/workshop for a new appointed PI1M Managers and Asst. Managers under ISITI-UNIMAS.